Upaya Guru Dalam Peningkatan Kualitas ESQ (Emotional & Spiritual Quotient) Siswa Melalui Pembelajaran PAI Di SMK Terpadu Assalam Durenan Trenggalek - Nafi’ah, Sayidatun; Azizah, Mar'atul (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2022)
The purpose of this study is to describe the efforts of PAI teachers in improving the ESQ quality of students at SMK Terpadu Assalam Durenan Trenggalek. This type of research is a qualitative field research (field research). This study used a qualitative descriptive research design. Data collection techniques using interview, observation, and documentation techniques. Furthermore, data analysis was carried out using qualitative descriptive analysis methods. The results showed that the teacher's efforts to improve the quality of students' ESQ through PAI learning at SMK Terpadu Assalam Durenan Trenggalek were quite effective and conducive, as seen from the behavior of students who showed an increase in ESQ quality and seen from the awareness of students to carry out habituation programs that were required by the school. The conclusion from the explanation above is that the teacher's efforts to improve the quality of students' ESQ through PAI learning at SMK Terpadu Assalam Durenan Trenggalek are quite good, and meet the objectives to be achieved, namely improving the quality of students' ESQ through PAI learning